Money, Banking, and the Canadian Financial System - Binhammer H. H. (Toronto Nelson Canada, 1988)
To assist students, especially in preparing for examinations, each diagram is accompanied by an explanatory citation which can serve as a review. Futhermore, review questions are found at the end of each chapter, and a glossary at the end of the book defines important terms and concepts. Boxes have been used to summerize some material, to present more difficult material, or simply to provide illustrations and examples. To assist instructor, Paul Pieper of Humber College has prepared an instructors manual which contains chapter overviews and test questions.
Keywords: 336